Photocatalytic synthesis of alkyl–alkyl sulfones via direct C(sp3)–H bond functionalization. Issue 13 (16th March 2023) - Lu, Wen-Hua; Yang, Dan; Wang, Guo-Qin; Wang, Ting; Zhou, Yuan-Xia; Jing, Lin-Hai
Abstract : A photoinduced TBADT-catalyzed one-pot, three-component strategy for the synthesis of alkyl-alkyl sulfones was reported. The developed methodology could tolerate broad functional groups and allow for the late-stage modification of complex molecules. Abstract : We report a highly efficient one-pot, three-component strategy for the construction of alkyl–alkyl sulfones through a photoinduced TBADT-catalyzed C(sp 3 )–H sulfonylation of unactivated hydrocarbon compounds. A wide range of commercially available hydrocarbon compounds and bioactive molecules can be successfully applied to the catalytic system, affording the corresponding alkyl–alkyl sulfones in good to excellent yields (>50 examples, up to 87% yield).